Food Habits of Snakehead, Channa Striata (Bloch), in Aquatic Habitats: a Review Literature - Rizha Bery Putriani; Nidya Kartini; Septi Malidda Eka Putri (Jurnal Biologi Tropis, 2023)
Snakehead fish as a fish of high economic value is currently still caught through nature where cork maintenance has not been widely done. Snakehead fish contains high protein, good for health can also for recover damaged. This investigation intends to produce findings from earlier research into the feeding patterns of snakehead fish (Channa striata) in aquatic environments. Because it can serve as a resource for the public and other parties in terms of ecological and biological studies as well as serve as a guide for activities involving the farming of snakehead fish, this study literature is fascinating to address the feeding habits of snakehead fish (Channa striata). Fish fries are the principal diet for carnivorous snakehead fish. when zooplankton or other tiny crustaceans are more commonly consumed by snakehead fish larvae. This disparity in eating patterns is determined by things including fish kind, age, food availability, environment, and fish size. Due to the lack of food, the effects of the season, and the time spent searching for food, snakehead fish are found to have an empty stomach in both their larval and adult stages.